Tangent hyperbolic circular frequency diverse array radars. Issue 3 (2nd March 2016) - Saeed, Sarah; Qureshi, Ijaz Mansoor; Khan, Waseem; Salman, Ayesha
Abstract : Frequency diverse array (FDA) with uniform frequency offset (UFO) has been in spot light of research for past few years. Not much attention has been devoted to non‐UFOs in FDA. This study investigates tangent hyperbolic (TH) function for frequency offset selection scheme in circular FDAs (CFDAs). Investigation reveals a three‐dimensional single‐maximum beampattern, which promises to enhance system detection capability and signal‐to‐interference plus noise ratio. Furthermore, by utilising the versatility of TH function, a highly configurable type array system is achieved, where beampatterns of three different configurations of FDA can be generated, just by adjusting a single function parameter. This study further examines the utility of the proposed TH‐CFDA in some practical radar scenarios.